2005
DOI: 10.1007/s00702-005-0275-7
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality in multiple sclerosis

Abstract: Sexuality and partnership have an important influence on the quality of life of every person and also on people with chronic disorders such as multiple sclerosis. The findings in literature show high evidence that people with multiple sclerosis experience high levels of sexual dysfunction, most of them with hypoactive sexual behaviour often associated with dissatisfaction in relationship, and also the partners seem to show lower sexual and partnership satisfaction. The most common problems in women are lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 47 publications
8
62
2
3
Order By: Relevance
“…Relapse of the disease itself doesn't seem to add to the number of SD symptoms [49]. Most of the affected patients experience sexual hypoactivitiy [50]. Beside reduced libido, men are often disabled by erectile dysfunction and premature ejaculation whereas women experience reduced libido, decreased vaginal lubrication and difficulties in reaching orgasm [45].…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relapse of the disease itself doesn't seem to add to the number of SD symptoms [49]. Most of the affected patients experience sexual hypoactivitiy [50]. Beside reduced libido, men are often disabled by erectile dysfunction and premature ejaculation whereas women experience reduced libido, decreased vaginal lubrication and difficulties in reaching orgasm [45].…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…This all contributes to MS patients having sexual intercourse less frequently compared to patients with other chronic diseases or healthy controls [47]. This is an important factor adding to relationship dissatisfaction felt by MS patients, as well as their partners [50]. Conceivably, there seems to be an association between cognition and impaired sexuality as patients with SD more often report symptoms such as memory and concentration problems [48].…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…Drugorzędowe dysfunkcje seksualne wynikają ze zmian niedotyczących bezpośrednio struktur powiązanych z aktywnością seksualną, które jednak wpływają na reaktywność seksualną. Uwarunkowania trzeciorzędowe dotyczą wpływów psychospołecznych i kulturowych na satysfakcję i funkcje seksualne [7][8][9][10].…”
Section: Wstępunclassified
“…The data of the patients with and without SD are compared in Table 3. D Di is sc cu us ss si io on n MS is a neurologic disorder with different courses and manifestations (9). SD is an important condition that affects the social life and quality of life of patients with a chronic disease such as MS (1,7,11,13). In the study by Valleroy et al (9) it was found that 75% of male patients had sexual problems and the most common symptom was difficulty in erection, 55% of patients had decreased genital sensation, 51% had fatigue, 48% decrease in libido, 44 % difficulties in ejaculation and orgasm, and 37% of had spontaneous erection or night erection.…”
Section: R Re Es Su Ul Lt Ts Smentioning
confidence: 99%
“…Unfortunately, discussion with the health workers about the changes in sexual habits are considered as taboo, and conversation with the patient and his/her partner is very difficult. As a result of this, sexual problems are neglected (11)(12)(13).…”
mentioning
confidence: 99%